PPM PENGEMBANGAN WISATA DESA DI DESA SUMBERMULYO KECAMATAN JOGOROTO KABUPATEN JOMBANG - Sayekti Suindyah Dwiningwarni; Chamariyah Chamariyah; Yurila Endah M; Sumita Widiyah Ningsih; Ananda Istiqomah Nur Fauziyah; Syamsiyah Yuli Dwi Andari (Universitas Pelita Harapan, 2023)
Sumber Mulyo is a village located in Jogoroto Jombang District. Sumber Mulyo Village has potential in the field of village tourism because this village is location in an area that has a history of